Radio, music, podcasts – BBC Sounds: Public service radio and podcasts in a platform world. (1st April 2020) - Berry, Richard
In 2018, the BBC announced plans to replace their long-established 'iPlayer Radio' service with a new platform called BBC Sounds. The new service was promoted as a single space where listeners can consume BBC radio, music and podcasts, creating a single point of interaction between audiences and content. This is, however, far more than an exercise in reframing public service radio content in a new app; it is also a practical application of these policies through the commissioning of content made for online, specifically, younger, audiences. This shift happens not only at a time where traditional broadcasters are exploring ways to re-engage younger listeners but as commentators search for the 'Netflix of Podcasts' This article explores the manner in which the BBC Sounds project is a response to current trends in the radio industry and to which it recognizes podcasting as an audio medium that is distinct from but institutionally connected to radio.